Resolving sub-internal limiting membrane haemorrhage mimicking as endogenous endophthalmitis - Pradeep Kumar Panigrahi; Loknath Mohanty; Japesh Thareja (Journal of Clinical and Scientific Research)
A 43-year-old male presented with painless loss of vision in the left eye (LE) of 5 days duration. The patient had been hospitalised for cerebral malaria and kidney infection. Streptococcus pneumoniae growth had been obtained from blood and urine cultures, and the patient had been diagnosed with endogenous endophthalmitis elsewhere. Best-corrected visual acuity (BCVA) in LE was 20/60, N12. Fundus examination showed a yellowish-white lesion in the macular area in LE. Optical coherence tomography revealed sub-internal limiting haemorrhage in LE. The patient was observed. Two weeks following presentation BCVA in LE improved to 20/32, N6 with almost complete resolution of lesion.